Social Capital Inequality and Subjective Wellbeing of Older Chinese - Appau, Samuelson; Awaworyi Churchill, Sefa; Smyth, Russell; Zhang, Quanda (Social indicators research, 2022)
Using longitudinal data from the China Family Panel Studies, this study provides insights on comparative wellbeing outcomes for older people who are institutionally segregated into clusters that produce uneven social capital. We present the first study that examines how institutionalized social capital inequality, measured by the social capital gap generated by hukou (household registration) status in China, affects the wellbeing of older people. Our results show that high levels of social capital inequality are associated with lower subjective wellbeing, measured by life satisfaction. This general conclusion is robust to a number of sensitivity checks including alternative ways of measuring subjective wellbeing and inequality. We also find that the negative relationship between social capital inequality and subjective wellbeing is strongest for people with a non-urban hukou living in urban areas. Our findings highlight the need for policies aimed at narrowing the social capital gap and the dismantling of institutional structures that hinder upward social capital mobility.